La didáctica de la lectura para mejorar el proceso de enseñanza-aprendizaje. - Lluglla Silva, Lizeth Alexandra (2021)
Within the research the quantitative approach is used, since it has a positivist paradigm, and its objective was testing theories found into the place where it was applied. The project research was feasible inasmuch as it had bibliographic information taken from several research works. Also, this is added the diagnosis done and its application in the explored place, here, the problem approach is described and the needs that children have to improve the teaching-learning process through didactics. To carry out this improvement a centered proposal on a specific objective was proposed. This began with teaching techniques in teacher charge, then, each reading was adjusted for being detailed in the three processes such as the pre-reading, reading and post-reading. The end of a closing activity with the aim of recording the new learning of the students. In addition, this was apprehensive since it allowed to compare and analyze the obtained results in this research, and, also it was comprehensive type, because it reveals everything which was found when approaching the research, it will not be experimental, because the existing theories were not modified. It is descriptive because was directed to the progressive differences of the students. The deductive method was used because it started from the problem observation, that is, the didactic process of reading as a learning source. On the other hand, as deduction is taking into account the given results of the empirical methods applied. Finally, the proposal was applied as an alternative solution to the didactics improvement of reading within the educational process.